TINJAUAN YURIDIS PERMOHONAN GANTI NAMA PADA AKTA KELAHIRAN DI PENGADILAN NEGERI KEFAMENANU DI TINJAU DARI UNDANG-UNDANG NOMOR 24 TAHUN 2013 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 23 TAHUN 2006 TENTANG ADMINISTRASI KEPENDUDUKAN - Koen, Felix Emanuel; Mauritsius, Darius; Pello, Helsina Fransiska (Petitum Law Journal, 2024)
The change of one's name in practice cannot be separated from the culture and customs that exist and grow in society. In Eastern culture, especially East Nusa Tenggara, it is still believed by some people. Giving the child an inappropriate name will make the child sickly and fragile. The solution is to rename it. After the name change process is complete, what they have to complete is the administrative process, which is to change the name on the birth certificate with a new name. For the recording of name changes themselves carried out based on court determinations, this can be seen from the provisions of Article 52 of Law Number 23 of 2006 concerning Population Administration juncto Article 93 paragraph (2) of Presidential Regulation Number 25 of 2008 concerning Requirements and Procedures for Population Registration and Civil Registration. This research is an empirical legal research, where empirical research is that researchers observe various realities that occur in the Kefamenanu District Court located in the North Central Timor Regency and review them based on the Law, derivative regulations related to the main problem that has been formulated previously by interviewing related parties and then the data that has been obtained is presented using the stages in it, namely coding, editing and tabulation as well as presented with qualitative descriptive.